An Intention-Driven Semi-autonomous Intelligent Robotic System for Drinking - Zhang, Zhijun; Huang, Yongqian; Chen, Siyuan; Qu, Jun; Pan, Xin; Yu, Tianyou; Li, Yuanqing (Frontiers in Neurorobotics, 2017)
In this study, an intention-driven semi-autonomous intelligent robotic (ID-SIR) system is designed and developed to assist the severely disabled patients to live independently. The system mainly consists of a noninvasive brain machine interface (BMI) subsystem, a robot manipulator and a visual detection and localization subsystem. Different from most of the existing systems remotely controlled by joystick, head- or eye-tracking, the proposed ID-SIR system directly acquires the intention from users' brain. Compared with the state-of-art system only working for a specific object in a fixed place, the designed ID-SIR system can grasp any desired object in a random place chosen by a user and deliver it to his/her mouth automatically. As one of the main advantages of the ID-SIR system, the patient is only required to send one intention command for one drinking task and the autonomous robot would finish the rest of specific controlling tasks, which greatly reduces the burden of patients. Eight healthy subjects attended our experiment, which contained 10 tasks for each subject. In each task, the proposed ID-SIR system delivered the desired beverage container to the mouth of the subject and then put it back to the original position. The mean accuracy of the eight subjects was $97.5%$, which demonstrated the effectiveness of the ID-SIR system.